2020
DOI: 10.1111/cpr.12784
|View full text |Cite
|
Sign up to set email alerts
|

Ophiopogonin D promotes bone regeneration by stimulating CD31hiEMCNhi vessel formation

Abstract: Objectives CD31hiEMCNhi vessels (CD31, also known as PECAM1 [platelet and endothelial cell adhesion molecule 1]; EMCN, endomucin), which are strongly positive for CD31 and endomucin, couple angiogenesis and osteogenesis. However, the role of CD31hiEMCNhi vessels in bone regeneration remains unknown. In the present study, we investigated the role of CD31hiEMCNhi vessels in the process of bone regeneration. Materials and Methods We used endothelial‐specific Krüppel like factor 3 (Klf3) knockout mice and ophiopog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…( 214 ) Treatment with ophiopogonin D, a Krüppel‐like factor‐3 (KLF3) inhibitor, enhances the abundance of type H vessels and accelerates bone healing. ( 215 ) A novel poly‐GLP‐1 molecule using a polymeric pro‐drug strategy was found to increase the number of type H ECs and promote bone formation in a mouse femoral defect model. ( 216 )…”
Section: Angiogenesis and Vascularization In Bone Tissue Engineeringmentioning
confidence: 99%
“…( 214 ) Treatment with ophiopogonin D, a Krüppel‐like factor‐3 (KLF3) inhibitor, enhances the abundance of type H vessels and accelerates bone healing. ( 215 ) A novel poly‐GLP‐1 molecule using a polymeric pro‐drug strategy was found to increase the number of type H ECs and promote bone formation in a mouse femoral defect model. ( 216 )…”
Section: Angiogenesis and Vascularization In Bone Tissue Engineeringmentioning
confidence: 99%
“…A recent study also confirmed the critical role of type H vessels in bone fracture healing, as type H vessels reappeared in the bone repair area of aged mice, together with increased osteoprogenitors and bone volume. 79 Furthermore, Ji et al also reported that the VEGF pathway mediated type H vessel angiogenesis and osseointegration in periimplant bone following injury. 80,81 Pharmacological blockade of the VEGF pathway led to the impairment of type H vessel formation, lower expression of osteogenic factors (including bone morphogenetic protein 2 and fibroblast growth factor 2), and decline of osteoprogenitors in the periimplant area.…”
Section: Osteoporosismentioning
confidence: 99%
“…In mammals, the bone is a kind of dynamic organ with a variety of essential functions, including protecting vital organs, attachment by skeletal muscle, storing mineral ions, and as an endocrine organ and an immune organ (Berger et al, 2019; Oldknow et al, 2015; Palmiter, 2017; Walsh et al, 2018). Our skeletal system undergoes a continuous remodeling cycle, carefully balances the activities of anabolic and catabolism to maintain its strength correctly and to accomplish the above tasks (Yang et al, 2020). Bone remodeling is done through the coordinated efforts of the three types of cells: bone marrow mesenchymal stem cell‐derived osteoblasts (OB) align on the bone surface and secrete bone matrix; matrix‐embedded OB further differentiate into persistent osteocytes (OCT), then the latter forms a mechanical sensing network within the bone and plays a vital role in paracrine signals; meanwhile, multinucleated osteoclasts (OC) from hematopoietic stem cells continually degrade and absorb the surrounding bone base (Abarrategi et al, 2018; Husain & Jeffries, 2017).…”
Section: Introductionmentioning
confidence: 99%